Development of an Amorphous Silica from Rice Husk Waste - Bangwar, D. K.; Saand, A.; Keerio, M. A.; Soomro, M. A.; Bhatti, N. (Engineering, Technology & Applied Science Research, 2017)
This article presents a study on the development of amorphous silica from Rice Husk (RH) waste. For ascertaining the optimum proportion of temperature and burning duration required for the development of an amorphous silica from RH waste, different Rice Husk Ash (RHA) samples, i.e. RHA (500oC-1.5hr), RHA (500oC-2hr), RHA (600oC-1.5hr), RHA (600oC-2hr), RHA (700oC-1.5hr), RHA (700oC-2hr), RHA (800oC-1.5hr), RHA (800oC-2) and RHA (900oC-1hr) were extracted by burning the husk at different temperatures and durations. Energy Dispersive Spectrometry (EDS) analysis was carried out for ascertaining the existence of main and insignificant elements in the RHAs samples and it was noticed that the extracting of silicon dioxide (SiO2) was exclusively dependent on the temperature and burning duration. After EDS, X-ray Diffraction (XRD) analysis was used to find out the crystalline and non-crystalline nature of obtained silica at different temperatures and burning durations. Through EDS and XRD, it has been found that that the extracted Rice Husk Ash at the temperature of 800oC for 2hr is rich in amorphous SiO2 content, i.e. 91.74% which meets the requirements of ASTM 618-03 for a pozzolanic material.